ARTISTIC FREEDOM AS A MANIFESTATION OF WILLPOWER - Rujina, Valeria (E-Journal VFU, 2024)
An analysis using the methodology of critical psychology regarding theconnection between censorship and social sanction in art and the necessary personality traits tooppose and overcome them. A short look into examples and predispositions of enforced restrictionon freedom of speech and efforts on guaranteeing it. Artists’ social contexts, personal copingabilities and ability to stand out as a predictor of willpower – postulated as a lead factor in personalartistic growth and popularity.
Keywords: society; art; personality traits; freedom of speech; censorship